20th century girl - Ferrendelli, Betta (Raton Range Raton, New Mexico)
Newspaper Article on the 90th birthday of Lucille Pavletich.
Master list item #: 40
File location is in the Raton File Cabinet
Keywords: Pavletich, Lucille; Pavletich, Frank; Pavletich, Nick; Club 85; Maverick Motel; Ma and Pa's World Place Motel; Local History; Biography; Life and Customs; Birthday; Celebration; Raton, New Mexico; Eagle Nest, New Mexico; Alabama; Springer, New Mexico; Maxwell, New Mexico; Wichita, Kansas; Summerville, Missouri; Cimarron, New Mexico